“Budi Pekerti” and its implications for the workplace - Ismail, Yusof (Kulliyyah of Economics and Management Sciences, IIUM, 2021)
Two languages are really different. They are unique in their own ways. They convey messages but do not necessarily share the same breadth and depth of meanings. ―Budi pekerti‖ has fewer hits when searched through Google Search compared to ―Character,‖ a close equivalent in English but the former conveys richer meaning than its latter counterpart. This chapter attempts to discuss the meaning of ―budi pekerti‖ and its implications for the workplace. It compares the meaning of related words of ―budi pekerti‖ and their equivalence in English because this Chapter is written in English for the benefit of Malay and English-speaking readers. Common ―budi pekerti‖ of Prophet Muhammad s.a.w. have been depicted in a comparative table in order to portray reference traits Muslims should emulate for practice.